Strategy for Utilizing Productive Zakat at BAZNAS Tanah Datar (Analysis Study using an Analytical Network Process Approach) - Yasirli, Ulva; Zainuddin, Zainuddin; Firdaus, Nil (Jurnal Ekonomi dan Perbankan Syariah, 2024)
The problem in this research is the Productive Zakat Utilization Strategy of BAZNAS Tanah Datar Regency. The problem topics are: priority problems for utilizing productive zakat, priority solutions to problems utilizing productive zakat, priority strategies for utilizing productive zakat. The aim of this research is to find priority problems in the utilization of productive zakat, find priority solutions to problems in the utilization of productive zakat, find and analyze priority strategies for the utilization of productive zakat using the Analytic Network Process (ANP) method. The results of this research are that the main priority OPZ problem is the low effectiveness of the productive zakat utilization program. The main priority problem for mustahik is the low motivation of mustahik to become muzakki. The main priority stakeholder/government problem is the lack of financial support for zakat institutions. Meanwhile, the strategy that is the main priority is improving skills and coaching mustahik in BAZNAS Tanah Datar Regency. Based on the results of the Analytic Network Process (ANP), it was found that the priority problem of the productive zakat utilization strategy lies in the OPZ problem with a higher agreement figure of 0.345. Then the priority solution obtained is the mustahik solution which also has an agreement figure of 0.329. The priority strategy with a higher agreement value for the productive use of zakat from BAZNAS Tanah Datar Regency is increasing skills and developing mustahik with a value of 0.336.